Ketika kejahatan berdaulat : sebuah pendekatan kriminologi, hukum dan sosiologi - Nitibaskara, Tubagus Ronny, 1943- ([Jakarta?] : Peradaban, 2001)
Crimes in Indonesia from criminological, legal, and sociological viewpoints; collected articles.
Includes bibliographical references (p. 261-263).
Keywords: Criminology -- Indonesia; Law -- Indonesia; Law enforcement -- Indonesia